(untitled) (Journal of Parents and Teachers, 2013)
The multinational Disney Corporation is built as an organization that creates educational and cultural curriculum, building a global culture in which our students are immersed in and participate. Disney not only sells its own products but it also sells values and identities. This article is about the need that exists of developing critical educative instruments that allow us to be conscious and ask ourselves about the role that media has in political, educative and social issues. It is important to insist on the necessity of having and educative subject in schools. This educative subject will bring us closer to the language of communication and to the critical analysis. Moreover, it is necessary to have time in the media to offer the possibility of learning to use and to read the communicative products.